Biofilm-mediated resistance to berberine in Escherichia coli - Yingfang Wang; Ruinan Zhang; Pengfei Wang; Wenlu Zhang; Zhongjie Li; Xinyue Pang; Fangfang Huang; Sensen Wang; Xingnuo Liu; He Zhang (Frontiers in Cellular and Infection Microbiology)
ObjectiveTo investigate the mechanism of biofilm-mediated resistance to berberine in Escherichia coli.MethodsThe resistance of berberine against E. coli was induced by 1/2 MIC (minimum inhibitory concentration). Biofilm formation was detected by crystal violet staining. The mRNA level was detected by RT-qPCR, and the gene csgD was determined. the csgD-overexpressed strain was constructed. We measured the MIC of berberine against E. coli, as well as biofilm formation and the expression of mRNA.ResultsThe MIC after berberine induction was more than 32 times than the MIC before induction. the biofilm was significantly increased at 24, 48 and 72 hours (p<0.01) after berberine induction. In addition, the amount of biofilm production at 24, 48 and 72 hours was 1.3, 1.51 and 1.98 times after berberine induction than that before induction, respectively. The expression of csgD gene was significantly increased (p=0.016) after induction compared with that before induction. the MIC of csgD-overexpressed strain was about 5.8 times that before induction. The expression of csgD gene was significantly increased (p=0.016), which was 5.8 times higher than that before induction. The MIC of csgD-overexpressed strain was 100 μg/mL. Biofilm formation in csgD-overexpressed strain was 2.9 times higher than that of the control. The expression of biofilm-related genes, bcsA, luxS and csgD, was 45, 22.5 and 1628 times higher than that of the control, respectively.ConclusionBerberine might increase biofilm formation by inducing the expression of csgD gene, which might result in drug resistance in E. coli.